Like a lake : a story of uneasy love and photography - Mavor, Carol, 1957- (Fordham University Press, 2020)
Like a Lake tells the story of Nico, his father (an Italian-American architect) and his mother (a Japanese-American sculptor). When the photographer Coda Gray befriends ten-year old Nico, the family is wrecked by its own perfection and readers find Northern California's post-war landscape giving way to fissures of alternative lifestyles.